Myocardial Perfusion and Metabolism After Transcoronary Ablation of Septum Hypertrophy (TASH) in Hypertrophic Obstructive Cardiomyopathy - Lerch, H.; Schäfers, M.; Gietzen, F.; Schäfers, K.; Kuwert, T.; Kuhn, H.; Schober, O. (Nuklearmedizin - NuclearMedicine, 1997)
Outflow obstruction constitutes a major problem in hypertrophic obstructive cardiomyopathy (HOCM) and may be treated by transcoronary injection of ethanol into septal arteries (transcoronary ablation of septum hypertrophy, TASH). We report on myocardial perfusion and glucose metabolism in a 50 year old man in whom TASH led to a reduction of septal thickness (9 vs. 26 mm), a sustained elimination of the outflow tract obstruction (resting gradient 0 vs. 60 mmHg; postES-gradient 10 vs. 145 mmHg) and a substantial clinical improvement (NYHA stage II vs. Il-lll) without impairment of global ventricular function (left ventricular ejection fraction 0.62 vs. 0.64). After TASH, perfusion and glucose metabolism were assessed by positron emission tomography (PET) using F-18-fluorodeoxyglucose (F-18-FDG) and Tc-99m-MIBI single photon emission tomography (SPECT). TASH results in matched reduction of perfusion and glucose consumption in a circumscribed area fed by the septal branch used for ethanol injection. No remote effects were observed. TASH leads to a sharply delineated septal reduction of perfusion and metabolism with consecutive reduction of septal thickness, a sustained elimination of the outflow tract obstruction, and a substantial clinical improvement without impairment of global ventricular function.
Keywords: Transcoronary Ablation of Septum Hypertrophy; Hypertrophic Obstructive Cardiomyopathy; Positron Emission Tomography; Single Photon Emission Tomography